Incline treadmill exercise suppresses pain hypersensitivity associated with the modulation of pro-inflammatory cytokines and anti-inflammatory cytokine in rats with peripheral nerve injury. (16th March 2017) - Tsai, Kun-Ling; Huang, Po-Ching; Wang, Li-Kai; Hung, Ching-Hsia; Chen, Yu-Wen
Highlights: Increased incline improved the anti-nociceptive effects of treadmill running. Inclined treadmill exercise attenuated levels of sciatic nerve pro-inflammatory cytokines. Inclined exercise increased the level of an anti-inflammatory cytokine. Abstract: We aimed to investigate the impact of 3 weeks of incline treadmill exercise (TE) on withdrawal responses elicited by thermal and mechanical stimuli, and on anti-inflammatory cytokine (interleukin-10, IL-10) and pro-inflammatory cytokines (IL-6 and tumor necrosis factor-alpha [TNF-α]) expression in the sciatic nerve of rats underwent chronic constriction injury (CCI). Group 1 received a sham-operation where the sciatic nerve was exposed but not ligated, while Group 2 underwent a sham-operation followed by exercising on an 8%-incline treadmill (TE8). Group 3 underwent only the CCI procedure, and Groups 4 and 5 underwent the CCI procedure followed by exercising on an 0%-incline treadmill (TE0) and TE8, respectively. Mechanical and thermal sensitivity and protein expression of IL-10, IL-6 and TNF-α were evaluated on postoperative days 12 and 26. Among the five groups, Group 5 displayed the least weight gain. Compared with Group 3, Group 5 had smaller decreases in mechanical withdrawal thresholds and heat withdrawal latencies. The CCI rats who received TE at 8% incline showed the downregulation of TNF-α and IL-6 in their sciatic nerves on postoperative days 12 and 26, as was found in the Group 3 rats. TE at 8% incline also prevented the downregulation of IL-10 in their sciatic nerves on postoperative day 12. The results demonstrated that increased incline improves the anti-nociceptive effects of treadmill running. Inclined exercise reduces the levels of pro-inflammatory cytokines and increases the level of an anti-inflammatory cytokine.